Recent research patterns and factors influencing eating behaviour amongst Malaysian youths: a scoping review - Abang Brian, Chen; Stephenson, Marcus L.; Tan, Ai Ling (Frontiers in Sustainable Food Systems, 2023)
Introduction: This scoping review focuses on the eating behaviour of Malaysian youths and the way in which their eating behaviour has been studied in recent years. There is a continuous need to comprehend the nature and structure of eating behaviour acquired during young adulthood as it is linked to the increasing number of adults who are overweight and obese. Past research has been employed using various methodologies in the analysis of different dimensions of eating behaviour amongst Malaysian youths. This enquiry reviewed recent studies to collate and map out the methodologies, areas of research and factors associated with eating behaviour amongst this target group. Methods: The 'preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews' (PRISMA-ScR) was adopted for this scoping review which utilised the EBSCOhost discovery platform and other such databases as Sage, ProQuest and Clinical Key™. Results: The search resulted in a total of 34 articles which were then analysed. This gave rise to the identification of four main dimensions of eating behaviour amongst Malaysian youth, namely: 'general adequacy and frequency of consumption of food groups'; 'consumption of specific food groups'; 'eating disorders'; and 'weight control'. Conclusion: The majority of the recent studies focused on the general adequacy and frequency of consumption of food groups studied using quantitative approaches across multi-ethnic target groups within the central region of Malaysia. This leaves room for more studies on the consumption of specific food groups, eating disorders and weight control that could be more ethnic-centric within other geographical areas within Malaysia. Many studies suggested the need to apply qualitative measures to investigate the contradictions arising from current research concerning the interplay between interpersonal, intrapersonal and environmental factors affecting eating behaviour amongst Malaysian youths.